2017
DOI: 10.1007/s00018-017-2547-4
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis and ferroptosis are alternative cell death pathways that operate in acute kidney failure

Abstract: Ferroptosis is a recently recognized caspase-independent form of regulated cell death that is characterized by the accumulation of lethal lipid ROS produced through iron-dependent lipid peroxidation. Considering that regulation of fatty acid metabolism is responsible for the membrane-resident pool of oxidizable fatty acids that undergo lipid peroxidation in ferroptotic processes, we examined the contribution of the key fatty acid metabolism enzyme, acyl-CoA synthetase long-chain family member 4 (ACSL4), in reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
216
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(238 citation statements)
references
References 43 publications
8
216
1
Order By: Relevance
“…In acute kidney failure, hemorrhagic stroke and nephrotoxic folic acid induce acute kidney injury, and inhibitors of ferroptosis (for example, ferrostatin-1) reduce the damage caused by cell sabotage. Ferrostatin-1 preserves renal function and decreases injury, oxidative stress and tubular cell death in mice with nephrotoxic folic acid-induced acute kidney injuries (17,58,59). Therefore, ferrostatin-1 may have a prophylactic effect in these non-neoplastic diseases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In acute kidney failure, hemorrhagic stroke and nephrotoxic folic acid induce acute kidney injury, and inhibitors of ferroptosis (for example, ferrostatin-1) reduce the damage caused by cell sabotage. Ferrostatin-1 preserves renal function and decreases injury, oxidative stress and tubular cell death in mice with nephrotoxic folic acid-induced acute kidney injuries (17,58,59). Therefore, ferrostatin-1 may have a prophylactic effect in these non-neoplastic diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Ferroptosis is a type of cellular sabotage that results in cell death, whereas apoptosis, pyroptosis and necroptosis are considered types of programmed cell death (16). Ferroptosis is not blocked by carbobenzoxy-valyl-alanyl-aspartyl-(O-me thyl)-fluoromethylketone, an inhibitor of caspase-dependent apoptosis and pyroptosis, or by necrostatin-1, an inhibitor of RIPK1-dependent necroptosis (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is a newly discovered form of regulated cell death that plays a major role in various diseases, including tumor, stoke, cold stress, acute kidney failure, and neural degeneration. 13,18,[29][30][31][32] As in TBI, a recent study reported that ferroptotic death possibly occurs at early time points after TBI in the pediatric rat CCI model due to elevated levels of 15-HpETE-PE in the brain cortex and hippocampus, along with increased expression of 15LO2 and decreased levels of GPX4. 19 However, the precise role of ferroptosis in adult rodents remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The role of ferroptosis as a cell death mechanism contributing to organ damage in sepsis has been hardly explored. Nevertheless, ferroptosis has been implicated in acute kidney failure and could be an important alternative cell death pathway during sepsis (Linkermann et al , ; Müller et al , ; Wenzel et al , ). The precise contribution and impact of each of above‐mentioned altered cellular processes have not been properly delineated and seem to depend on lipid composition and cell type (Ghosh & Rodrigues, ).…”
Section: Sepsis and Fatty Acid Metabolismmentioning
confidence: 99%